Assessing biases of information contained in pedigrees for the classification of BRCA-genetic variants: a study arising from the ENIGMA analytical working group. Issue 1 (December 2016) - Kerkhofs, C.; Spurdle, A.; Lindsey, P.; Goldgar, D.; Gómez-García, E.
Abstract Purpose One way of evaluating family history (FH) for classifyingBRCA1/2 variants of uncertain clinical significance (VUS) is to assess the "BRCA-ness" of a pedigree by comparing it to reference populations. The aim of this study was to assess if prediction ofBRCA pathogenic variant (mutation) status based on pedigree information differed due to changes in FH since intake, both in families with a pathogenic variant (BRCAm ) and in families with wild-type (BRCAwt ). Patients and methods We compared theBRCA1/2 pathogenic variant detection probabilities between intake and most recent pedigree forBRCAm families (n = 64) andBRCAwt (n = 118) using the BRCAPRO software program. Results Follow-up time between intake and most recent pedigree was significantly longer (p < 0.001) in theBRCAm compared to theBRCAwt families. AmongBRCAwt families, the probability to detect a pathogenic variant did not change over time. Conversely, among theBRCAm, this probability was significantly higher for most recent vs. intake pedigree (p = 0.006). Conclusion Clinical scores change significantly over time forBRCAm families. This may be due to differences in follow-up, but also to differences in cancer risks from carrying a pathogenic variant in a highly penetrant gene. To reduce bias, models for VUS classification should incorporate FH collected at intake.